The Completion of Filing A Claim Ex Gratia Sharia Life Insurance - Lukman Anthoni; Yusuf (Journal of Research in Business, Economics, and Education, 2020)
The difference in the process of claim settlement with the standard and Ex Gratia categories is the core of this study, so that researchers can find out the difference in the work procedure for filing a standard claim with the submission of claims with the Ex Gratia category. The research instrument of this research uses documentation, interviews and literature studies with descriptive qualitative research methods by conducting research on the object of PT XYZ sharia life insurance research as well as describing the workflow and process carried out in the settlement of claims of the Ex Gratia category. Conclusions regarding the filing of an Ex Gratia claim are made after the results of the claims analysis are completed with the decision rejected by the claims department. The Ex Gratia claim process is carried out by re-submitting a claim that has been rejected. The decision to file an Ex Gratia appeal will be submitted to management and the results will be forwarded to the Policy Holder. Prevention of filing an Ex Gratia claim early can be done by adjusting the product specifications according to the expectations of policyholders. The frequency of filing claims for the Ex Gratia category is expected to be controlled or can be limited considering the use of funds for settling Ex Gratia claims originating from company funds, because in essence the submission of the claim is rejected because it does not comply with the provisions of the Sharia insurance policy claim.